Consumer Protection in Indonesia's Thrift Fashion Boom: Challenges, Obstacles, and Policy Implications - Soesilo, Galih Bagas; Rahmat, Al Fauzi; Sapardiyono, Sapardiyono; Siregar, Sabilillah Rais (Journal of Judicial Review, 2025)
The increasing sales and high market demand for Thrift Fashion pose several risks, particularly concerning consumer safety and the sustainability of the business climate within the same market. Imported second-hand clothing may be classified as hazardous goods or products due to its free circulation without adequate quality control. This research aims to examine the challenges, obstacles, and policy implications in addressing the sales of Thrift Fashion in Indonesia. The methodology employed in this study is purely normative legal research, relying solely on secondary data sources. The findings indicate that Thrift Fashion is explicitly prohibited in Indonesia, as stated in Law Number 7 of 2014 concerning Trade, Law Number 8 of 1999 concerning Consumer Protection, and Regulation of the Minister of Trade Number 40 of 2022. The issue surrounding Thrift Fashion extends beyond the actions of consumers and business actors; it is also influenced by insufficient law enforcement to prevent the circulation of such goods. In response to this, it is essential to adopt effective solutions to address the proliferation of Thrift Fashion. One such solution is to educate consumers about the risks associated with the violation of product usage rights and to raise awareness among business actors at various levels regarding their obligation to ensure the quality of the products they sell. The government could also offer compensation or targeted subsidies to business actors engaged in the Thrift Fashion trade, enabling them to transition to alternative businesses when their products are confiscated and destroyed.